The effect of exposure to long working hours on alcohol consumption, risky drinking and alcohol use disorder: A systematic review and meta-analysis from the WHO/ILO Joint Estimates of the Work-related Burden of Disease and Injury - Daniela V. Pachito; Frank Pega; Jelena Bakusic; Emma Boonen; Els Clays; Alexis Descatha; Ellen Delvaux; Dirk De Bacquer; Karoliina Koskenvuo; Hannes Kröger; Marie-Claire Lambrechts; Carolina O.C. Latorraca; et al. (Environment International, 2021)
Background: The World Health Organization (WHO) and the International Labour Organization (ILO) are developing Joint Estimates of the work-related burden of disease and injury (WHO/ILO Joint Estimates), with contributions from a large network of experts. Evidence from mechanistic data suggests that exposure to long working hours may increase alcohol consumption and cause alcohol use disorder. In this paper, we present a systematic review and meta-analysis of parameters for estimating the number of deaths and disability-adjusted life years from alcohol consumption and alcohol use disorder that are attributable to exposure to long working hours, for the development of the WHO/ILO Joint Estimates. Objectives: We aimed to systematically review and meta-analyse estimates of the effect of exposure to long working hours (three categories: 41–48, 49–54 and~≥55~h/week), compared with exposure to standard working hours (35–40~h/week), on alcohol consumption, risky drinking (three outcomes: prevalence, incidence and mortality) and alcohol use disorder (three outcomes: prevalence, incidence and mortality). Data sources: We developed and published a protocol, applying the Navigation Guide as an organizing systematic review framework where feasible. We searched electronic bibliographic databases for potentially relevant records from published and unpublished studies, including the WHO International Clinical Trials Register, Ovid MEDLINE, PubMed, Embase, and CISDOC on 30 June 2018. Searches on PubMed were updated on 18 April 2020. We also searched electronic grey literature databases, Internet search engines and organizational websites; hand-searched reference list of previous systematic reviews and included study records; and consulted additional experts. Study eligibility and criteria: We included working-age (≥15~years) workers in the formal and informal economy in any WHO and/or ILO Member State but excluded children (<15~years) and unpaid domestic workers. We considered for inclusion randomized controlled trials, cohort studies, case-control studies and other non-randomized intervention studies with an estimate of the effect of exposure to long working hours (41–48, 49–54 and~≥55~h/week), compared with exposure to standard working hours (35–40~h/week), on alcohol consumption (in g/week), risky drinking, and alcohol use disorder (prevalence, incidence or mortality). Study appraisal and synthesis methods: At least two review authors independently screened titles and abstracts against the eligibility criteria at a first stage and full texts of potentially eligible records at a second stage, followed by extraction of data from publications related to qualifying studies. Two or more review authors assessed the risk of bias, quality of evidence and strength of evidence, using Navigation Guide and GRADE tools and approaches adapted to this project. Results: Fourteen cohort studies met the inclusion criteria, comprising a total of 104,599 participants (52,107 females) in six countries of three WHO regions (Americas, South-East Asia, and Europe). The exposure and outcome were assessed with self-reported measures in most studies. Across included studies, risk of bias was generally probably high, with risk judged high or probably high for detection bias and missing data for alcohol consumption and risky drinking. Compared to working 35–40~h/week, exposure to working 41–48~h/week increased alcohol consumption by 10.4~g/week (95% confidence interval (CI) 5.59–15.20; seven studies; 25,904 participants, I2 71%, low quality evidence). Exposure to working 49–54~h/week increased alcohol consumption by 17.69~g/week (95% confidence interval (CI) 9.16–26.22; seven studies, 19,158 participants, I2 82%, low quality evidence). Exposure to working~≥55~h/week increased alcohol consumption by 16.29~g/week (95% confidence interval (CI) 7.93–24.65; seven studies; 19,692 participants; I2 82%, low quality evidence). We are uncertain about the effect of exposure to working 41–48~h/week, compared with working 35–40~h/week on developing risky drinking (relative risk 1.08; 95% CI 0.86–1.36; 12 studies; I2 52%, low certainty evidence). Working 49–54~h/week did not increase the risk of developing risky drinking (relative risk 1.12; 95% CI 0.90–1.39; 12 studies; 3832 participants; I2 24%, moderate certainty evidence), nor working~≥55~h/week (relative risk 1.11; 95% CI 0.95–1.30; 12 studies; 4525 participants; I2 0%, moderate certainty evidence). Subgroup analyses indicated that age may influence the association between long working hours and both alcohol consumption and risky drinking. We did not identify studies for which we had access to results on alcohol use disorder. Conclusions Overall, for alcohol consumption in g/week and for risky drinking, we judged this body of evidence to be of low certainty. Exposure to long working hours may have increased alcohol consumption, but we are uncertain about the effect on risky drinking. We found no eligible studies on the effect on alcohol use disorder. Producing estimates for the burden of alcohol use disorder attributable to exposure to long working hours appears to not be evidence-based at this time.
Keywords: 330; Global burden of disease; Occupational health; Long working hours; Alcohol consumption; Systematic review; Meta-analysis